Performance of the glazed facades with a flowing sustainable water film exposed to direct solar radiation under the Malaysian climate / Abdultawab Mohammed Qahtan - Abdultawab, Mohammed Qahtan (2012)
On the east and west orientations of the glazed buildings in the tropics where the solar altitude is low, the solar energy transmittance can not be effectively controlled by shading, except by blocking most of the glazed facades. Wherein, the daylight would be sacrificed. Based on this premise, to reduce the transmittance of solar energy without sacrificing daylight, the appropriate solution is the use of high performance insulated glazing system with spectrally selective coatings that distinguish between visible range (daylight) and infrared range (heat). Nevertheless, the drawback is its high capital cost. This study seeks to improve the control of total solar energy transmittance by exploitation the potential of recycled elements in such tropical countries combined with low cost glazing. The study examines the effectiveness of Sustainable Glazed Water Film (SGWF) in reducing the solar heat transmittance and maximizing the solar light transmittance indoors. The Malaysian climate and green-glazed buildings have been discussed to provide a direction to select the appropriate alternative solar control that copes with the east and west glazed facades in the tropical countries. SGWF was suggested as an alternative solar control and was numerically and experimentally investigated on glazed facades of west orientation, in the University of Malaya’s campus. The experiments involved a study of three parameters namely: water flow rate, types of glazing, and the solar radiation intensity. The effect of water film thickness was also discussed. Two full-scale rooms were used, one as a reference room, with a fixed configuration, and the other as a test room, which could be configured in different ways. It was found that the flowing water film on the glazed facades lowers the glazing surface temperature by 7.2 to 14°C (average) and absorbs a portion of the solar energy xx thus resulting in a decrease in the indoor temperature by 2.2 to 4.1°C (average). On the other hand, although about 70% of the short infrared ranging between 1300nm and 2500nm are totally absorbed by the thin water film, the solar radiation transmittance behind the SGWF facade increased by 2% to 6.8% compared to the facade without water film. This is because the water film acts as an anti-reflective coat to transmit the entire visible light range hence reducing its reflection outwards compared to dry glass. It was concluded that the sustainable spectrally selective feature of the SGWF improved the performance of glazed buildings by reducing the solar heat (or infrared) transmittance and maximizing the solar light (or visible light) transmittance indoors. From the study it can be summarised that significant energy could be saved by adopting the SGWF facade. It was observed that, (a) a reduction of 24.6% of the total energy cooling could be achieved as compared to an identical system without water film; (b) the reduction in glass surface temperatures contributed to the reduction of surrounding temperature (heat island effects) that affects the indoor environment; and (c) the increase in the visible light transmittance resulted in the reduction of the energy required for artificial lighting.